Implementation and Role of Double Taxation Agreements (Tax Treaties) in International Transactions - Adhar Putra Setiawan; Rieska Maharani; Asyidatur Rosmaniar; Marista Oktaviani (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2026)
Purpose: This study examines the role and implementation of Double Taxation Agreements (DTAs), focusing on their effectiveness in preventing double taxation, encouraging foreign investment, and addressing tax avoidance practices. Methodology: The research uses a qualitative approach with a normative juridical method. Data were collected through library research and analyzed using statutory and conceptual approaches, covering domestic tax regulations, tax treaties, the OECD Model Tax Convention, the Base Erosion and Profit Shifting (BEPS) framework, and the Multilateral Instrument (MLI). Findings: The results show that tax treaties contribute to reducing double taxation, increasing legal certainty, and supporting foreign direct investment in Indonesia. The adoption of BEPS standards and the MLI has strengthened Indonesia’s international tax framework and improved transparency in cross-border taxation. However, challenges remain, including treaty shopping, profit shifting, and regulatory inconsistencies that may reduce the effectiveness of treaty implementation. Implication: The study emphasizes the need to strengthen anti-abuse measures, improve tax administration, and harmonize domestic regulations with international tax standards to ensure a fair and sustainable taxation system. Originality: This study provides an integrated analysis of tax treaty implementation in Indonesia by combining legal and international taxation perspectives. It highlights the dual function of tax treaties as instruments for investment promotion while also identifying their potential misuse for tax avoidance.